Pengaruh Kemampuan Orientasi Mobilitas terhadapLingkungan Sekolah bagi Anak Disabilitas NetraSedang melalui Penggunaan Tongkat Putih - Aisa, Siti; Sugihartatik, Sugihartatik; Prystiananta, Nostalgianti Citra (JOEAI (Journal of Education and Instruction), 2025)
This study aims to analyze the effectiveness of using a white cane in improving the orientation and mobility abilities of children with moderate visual disabilities in the school environment. The method used was Single Subject Research (SSR) with an A-B design, involving one class V student at SLB Negeri Cindogo, Bondowoso. The study results showed a significant increase from an average score of 57.5% in the baseline phase to 90.83% after the intervention. The conclusion is that using a white cane facilitates physical movement and supports increasing independence and self-confidence in children with visual disabilities.   Keywords: Visual Disabilities, Independence, Mobility, Orientation, White Cane